Classical stretch. Posture & pain-relief for beginners ; Mobility & bone strengthening for beginners [videorecording (DVD)] (Essentrics age reversing workouts for beginners, 2015)
"In order to maintain our youth and vitality-we need to remain pain-free, energetic, and have correct posture. Miranda's gentle, full-body beginner workouts will help you achieve these goals by unlocking your body, boosting your energy and setting you on the path towards aging backwards. As discussed in Miranda's New York Times bestselling book, Aging Backwards, these two Essentrics workouts will engage every muscle in your body, liberate your joints and improve your overall health."--Container.